2019
DOI: 10.1111/zph.12613
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile shedding by healthy dogs in Nigeria and Malawi

Abstract: The objectives of this study were to determine the prevalence and characteristics of Clostridium difficile shedding in owned dogs in Nigeria and Malawi. Clostridium difficile was isolated from 31/120 (26%) dogs in Nigeria and 11/92 (12%) dogs in Malawi (p = 0.012). Overall, 22/42 (52%) isolates were toxigenic; 17/31 (55%) from Nigeria and 5/11 (45%) from Malawi. All toxigenic isolates possessing tcdA and tcdB, and only one also possessed cdtA/B. Sixteen different ribotypes were found, ten (63%) of which were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The overall prevalence of C. difficile (11.8%) in dogs and the percentage of toxigenic isolates (73.7%) found in our study are consistent with previous findings (Hussain et al, 2015; Rabold et al, 2018; Stone et al, 2016; Usui et al, 2016; Weese et al, 2010, 2019). Prior antibiotic treatment was not a significant risk factor for shedding C. difficile , which was in contrast to other authors' findings (Clooten et al, 2008; Rabold et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The overall prevalence of C. difficile (11.8%) in dogs and the percentage of toxigenic isolates (73.7%) found in our study are consistent with previous findings (Hussain et al, 2015; Rabold et al, 2018; Stone et al, 2016; Usui et al, 2016; Weese et al, 2010, 2019). Prior antibiotic treatment was not a significant risk factor for shedding C. difficile , which was in contrast to other authors' findings (Clooten et al, 2008; Rabold et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies pointed to pets as potential sources of CA‐CDI (Rabold et al, 2018; Stone et al, 2016). In healthy dogs, C. difficile presence ranges between 3.4% and 30% (Hussain et al, 2015; Rabold et al, 2018; Schneeberg et al, 2012; Stone et al, 2016; Usui et al, 2016; Weese et al, 2019). Although toxigenic and non‐toxigenic isolates were detected in dogs, including the epidemic hypervirulent PCR ribotype (RT) 027 (Rabold et al, 2018), genomic information on C. difficile strains isolated from animals other than livestock and horses is scarce (Knight et al, 2019; Knight & Riley, 2019; Rodriguez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported a link between diarrheal disorders in dogs and the presence of toxigenic strains of C. difficile in feces [35,51,58]. However, the prevalence rates of toxigenic C. difficile found in apparently healthy animals [28,29] make it difficult to determine whether the disease is subclinical in these animals or if they are only carriers. Weese et al [10] contended that, despite being asymptomatic carriers, dogs can become symptomatic carriers when exposed to risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show different rates of isolation for C. difficile, ranging from 0 to 18% for diarrheal [1,2,[13][14][15] and non-diarrheal dogs [8,[16][17][18][19], reaching 58% in association with specific groups, such as age [20][21][22] and contact with human or veterinary health facilities [23][24][25][26]. Due to the presence of toxigenic C. difficile strains in asymptomatic animals and the failure to reproduce the CDI in healthy dogs with or without antibiotic treatment [27], the role of C. difficile in canine enteric disease remains unknown [28,29]. There have been some reports of toxigenic strains of C. difficile being associated with diarrhea in dogs [1,2,4,[13][14][15][16][30][31][32][33], including an outbreak in a veterinary hospital [34].…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen studies involved multiple states, while one study did not specify the states covered in the study [39]. There was only one paper that screened samples from Nigeria and Uganda [40].…”
Section: Location Of Studiesmentioning
confidence: 99%